Dynamics of influenza in tropical Africa: Temperature, humidity, and co‐circulating (sub)types. Issue 4 (17th April 2018) - Yang, Wan; Cummings, Matthew J.; Bakamutumaho, Barnabas; Kayiwa, John; Owor, Nicholas; Namagambo, Barbara; Byaruhanga, Timothy; Lutwama, Julius J.; O'Donnell, Max R.; Shaman, Jeffrey
Abstract : Background: The association of influenza with meteorological variables in tropical climates remains controversial. Here, we investigate the impact of weather conditions on influenza in the tropics and factors that may contribute to this uncertainty. Methods: We computed the monthly viral positive rate for each of the 3 circulating influenza (sub)types (ie, A/H1N1, A/H3N2, and B) among patients presenting with influenza‐like illness (ILI) or severe acute respiratory infections (SARI) in 2 Ugandan cities (Entebbe and Kampala). Using this measure as a proxy for influenza activity, we applied regression models to examine the impact of temperature, relative humidity, absolute humidity, and precipitation, as well as interactions among the 3 influenza viruses on the epidemic dynamics of each influenza (sub)type. A full analysis including all 4 weather variables was done for Entebbe during 2007‐2015, and a partial analysis including only temperature and precipitation was done for both cities during 2008‐2014. Results: For Entebbe, the associations with weather variables differed by influenza (sub)type; with adjustment for viral interactions, the models showed that precipitation and temperature were negatively correlated with A/H1N1 activity, but not for A/H3N2 or B. A mutually negative association between A/H3N2 and B activity was identified in both Entebbe and Kampala. Conclusion: Our findings suggest that key interactions exist among influenza (sub)types at the population level in the tropics and that such interactions can modify the association of influenza activity with weather variables. Studies of the relationship between influenza and weather conditions should therefore determine and account for co‐circulating influenza (sub)types.